Prototype Autonomous Rover Pembersih Sampah Pantai menggunakan ArduPilot - Anto, Adhy Febry; Sukardiyono, Totok (Elinvo (Electronics, Informatics, and Vocational Education), 2019)
Indonesia has the second longest coastline in the world. On the other hand, Indonesia is the second largest contributor to marine waste in the world. Coastal cleanliness needs to be maintained so that it becomes an attraction for tourism and to protect the marine ecosystem. This article describes the results of testing devices that can be used to clean beaches. Research carried out by the development method. An autonomous beach garbage cleaning rover is a beach trash sweeper robot equipped with GPS, compass, telemetry, ArduPilot as a navigation and communication system when the robot operates. This robot moves using 2 DC motors with torque of ± 4 kg. The robot is also equipped with a conveyor that functions to sweep plastic debris on the beach. The test results show that the robot can go according to the specified path, according to the coordinates entered (100% accuracy) and be able to transport plastic waste. This is because the motor used has a small torque, so it is not able to lift large objects. The next robot development can be done in terms of: identifying the capacity of robots to accommodate various types of waste, testing the ability of robots to clean waste, the use of solar cells, and trajectory management systems.